Pengaruh Online Customer Review Dan Promosi Gratis Ongkos Kirim Terhadap Keputusan Pembelian Produk Sunscreen Wardah Di E-Commerce Shopee Dengan Minat Beli Sebagai Variabel Intervening (Studi Kasus Pada Konsumen Produk Sunscreen Wardah Di Kecamatan Medan - Br.T, Rahayu Purwaseh; Purnama, Nadia Ika (JURNAL MANAJEMEN DAN BISNIS, 2025)
influence of free shipping promotions on purchasing decisions, the influence of online customer reviews on purchasing interest, the influence of free shipping promotions on purchasing interest, the influence of purchasing interest on purchasing decisions, the influence of online customer reviews on purchasing decisions mediated by purchasing interest and the influence of free shipping promotions on purchasing decisions mediated by purchasing interest. This study uses a research method with a quantitative approach that is associative The data collection technique used a questionnaire, which was then tested for validity and reliability to determine whether the results of the questionnaire distributed were feasible or not. The data analysis technique used the SmartPLS version 4 application with outer model and inner model tests. The results of this study indicate that online customer reviews have a positive and significant influence on purchasing decisions, free shipping promotions have a positive and significant influence on purchasing decisions, online customer reviews have a positive and significant influence on purchasing interest, free shipping promotions have a positive and significant influence on purchasing interest, purchasing interest has a positive and significant influence on purchasing decisions, online customer reviews have a positive and significant influence on purchasing decisions mediated by purchasing interest and free shipping promotions have a positive and significant influence on purchasing decisions mediated by purchasing interest.